Implementing Virtual Simulations to Support English Language Learning in EFL Context - Erfina Maulidah Khabib; Suci Muliana; Vilya Lakstian Catra Mulia; Paulina Deby Putri Indrawati (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This study investigated students’ responses toward the implementation of virtual simulations in English language learning within an English as a Foreign Language (EFL) context. The primary objectives were to explore the dimensions of student responses, analyse the factors influencing their engagement, and identify the language components most significantly affected during the simulation process. Adopting a qualitative case study design, the research was conducted with 10 participants at Pasadena Hotel College. Data were collected through classroom observations, semi-structured interviews, documentation, and supplementary questionnaires to ensure comprehensive data triangulation. The data were analysed using qualitative content analysis consisting of data reduction, data display, and conclusion drawing to identify affective, cognitive, and psychomotor response patterns. The virtual simulations included web-based platforms, game-based simulations, and the PRAKTIKA application within hospitality-related learning scenarios. The findings revealed that students demonstrated predominantly positive affective, cognitive, and psychomotor responses toward the use of virtual simulations. The simulations increased students’ motivation, confidence, and classroom engagement, while speaking and vocabulary were identified as the language components most significantly enhanced. Furthermore, perceived realism, ease of use, and instructional guidance emerged as the main factors influencing students’ responses and engagement throughout the learning process. These findings contribute to the growing literature on technology-enhanced language learning by demonstrating that virtual simulations function as interactive learning environments that support meaningful language learning in vocational EFL contexts and provide practical implications for educators integrating digital technologies into English language instruction.